2007
DOI: 10.1248/bpb.30.1065
|View full text |Cite
|
Sign up to set email alerts
|

Knock-down of Sorcin Induces Up-regulation of MDR1 in HeLa Cells

Abstract: In our previous study, the MDR1/Pglycoprotein-overexpressing multidrug resistant subline, Hvr100-6, was established from the human cervical carcinoma cell line HeLa-Ohio (HeLa) by stepwise exposure to an anti-microtubule agent, vinblastine sulfate, a typical substrate of MDR1. Their gene and protein expression profiles were analyzed herein, and 148 genes were identified to be differentially expressed by cDNA microarray analysis. The up-regulation of sorcin, a soluble resistance-related calcium-binding protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…Some evidence suggests that sorcin may be responsible for inducing MDR in human tumors (17)(18)(19)(20)(21)(22)(23), but no information is available on the specific function of the 22 kDa isoform in CRC drug resistance. Thus, pRC-or 22 kDa sorcin-HCT-116-stable transfectants ( Supplementary Fig.…”
Section: The 22 Kda Isoform Of Sorcin Is Involved In Mdr In Human Crcmentioning
confidence: 99%
See 2 more Smart Citations
“…Some evidence suggests that sorcin may be responsible for inducing MDR in human tumors (17)(18)(19)(20)(21)(22)(23), but no information is available on the specific function of the 22 kDa isoform in CRC drug resistance. Thus, pRC-or 22 kDa sorcin-HCT-116-stable transfectants ( Supplementary Fig.…”
Section: The 22 Kda Isoform Of Sorcin Is Involved In Mdr In Human Crcmentioning
confidence: 99%
“…19) and CHOP regimen in diffuse large B-cell lymphoma (20). Other reports suggest a correlation between the expression of sorcin and the MDR1/P-glycoprotein: it has been shown that sorcin knockdown induces the upregulation of MDR1 in HeLa cells (21); by contrast, a direct correlation between sorcin and MDR1 expression and a role of sorcin in inducing a MDR phenotype has been observed in human leukemia and gastric carcinoma cells (22,23). Finally, recent studies in oral squamous cell carcinoma, NSCLC, and acute myeloid leukemia suggest that sorcin may be responsible for drug resistance and poor prognosis (19,24,25).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The level of mRNA for galectin-1 was measured by the quantitative real time RT-PCR method as described previously [13,14]. Forward primers, reverse primers and TaqMan probes are listed in Table 2.…”
Section: Quantitative Real Time Rt-pcrmentioning
confidence: 99%
“…The overexpression of sorcin genes may just be coincidental with the amplification of MDR (21). Other conflicting results suggested that sorcin might be independently involved in mediating MDR (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%